Genetic aspects of productive and reproductive traits in a Murrah buffalo herd in São Paulo, Brazil - Tonhati, Humberto [UNESP]; Vasconcellos, F. B.; Albuquerque, L. G. (Blackwell Wissenschafts Verlag Gmbh, 2000)
This study investigated genetic trends of some productive and reproductive traits in a herd of Murrah buffalo raised in São Paulo, Brazil. Variance components for milk production (Mr), length of lactation (LL), calving interval (CI) and age of first calving (AFC) were estimated by che restricted maximum likelihood method, using an animal model. Estimated heritability values were 0.38; 0.01; 0.10 and 0.20 for MP, LL, CI and AFC, respectively. Estimated repeatability values were 0.50, 0.13 and 0.20 for MP, LL and CI, respectively. Means of predicted breeding values for cows, dams and sires according to calving year and the genetic correlations were presented.